Dynamic physical education for secondary school students - Pangrazi, Robert P. (Allyn and Bacon, 1997)
This book is divided into five sections: Justifying a Physical Education Program; Designing a Physical Education Program; Teaching a Physical Education Program; Developing a Total Program; Implementing Instructional Activities.